The Effects of Land Use Changes on the Distribution of the Chinese Endemic Species of Brown-Eared Pheasant - Zhao, Yue; Dang, Cuiying; Liu, Yaoguo; Xu, Shicai; Zhu, Mengyan (Diversity (Basel), 2024)
The Chinese government has undertaken a significant forest restoration project, leading to a notable increase in forested areas. Despite this achievement, there is uncertainty regarding its impact on wildlife protection. To assess this, we utilized high-resolution remote sensing data to gather information on land use, bioclimatic conditions, geography, and human activity. This information was used to model and analyze changes in suitable habitats for Chinese endemic brown-eared pheasants over the past 30 years to determine the effects of the forest restoration project on wildlife habitats. Our analysis revealed that although the suitable habitat area for the brown-eared pheasant has expanded, the increased forested area did not influence their distribution. Our study also found that increasing elevation and decreasing grassland area in landscape patches promoted the distribution of brown-eared pheasants. Furthermore, the annual variation of the min temperature of coldest month and annual precipitation is an important factor affecting the suitable habitat distribution of brown-eared pheasants. Research showed that the suitable habitat of brown-eared pheasant is seriously fragmented, and the connectivity between habitats should be strengthened in the future. Based on our findings, we believe that existing forest restoration project policies cannot effectively protect wildlife due to neglecting key environmental factors at the landscape scale. Therefore, we recommend developing refined land use management policies at the landscape level to guide future ecological protection and biodiversity conservation. These findings significantly affect policy and future research on wildlife protection and forest restoration.